Comparative Study on the Effect of Zinc and Probiotic Therapy Versus Zinc Supplementation Alone on the Duration of Acute Watery Diarrhea in Children - Mateen, Maryam; Roshan, Emran; hayyat, Muhammad khizar; Rehman Akram, Abdul; Nasrin, Tahira; Bakhtawar Khan, Saad (Biological and Clinical Sciences Research Journal, 2025)
Diarrhea remains a leading cause of morbidity and mortality among children worldwide. Numerous studies have investigated the effects of zinc and probiotics in reducing the duration and severity of acute watery diarrhea. Objective: This study aimed to compare the efficacy of zinc-probiotic combination therapy with zinc-only therapy in managing acute watery diarrhea in pediatric patients. Methodology: Conducted at the Department of Pediatrics, Sughra Shafi Medical Complex, Narowal, from March 10, 2023, to August 10, 2024, the study enrolled 80 children diagnosed with acute watery diarrhea, who were randomly assigned into two groups. Group A received oral zinc, low osmolarity ORS, and continued nutritious feeding, while Group B was given Enflor sachets in addition to zinc and ORS. The duration of diarrhea was recorded, and data analysis was performed using SPSS v25.0. A t-test was used to compare the duration of diarrhea between the two groups, with statistical significance set at p ≤ 0.05. Results: The average age in Group A was 38.3±10.5 months, and in Group B, it was 38.6±10.1 months. The duration of diarrhea in Group A was 31.35±2.338 hours, compared to 24.08±2.495 hours in Group B, with a significant difference (p = 0.0001). Conclusion: The combination of probiotics and zinc was more effective than zinc alone in reducing the duration of acute diarrhea in children, suggesting a significant improvement in treatment outcomes.